1999
DOI: 10.1111/j.1540-8159.1999.tb00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter Defibrillators and Cellular Telephones: Is There Any Interference?

Abstract: The aim of our study was to consider cellular telephone interference using different cellular telephones and implantable cardioverter defibrillator (ICD) models. Thirty (26 men, 4 women) patients with ICDs were considered during follow-up. The ICD models were: Telectronics (7), CPI (7), Medtronic (7), Ventritex (5), and Ela Medical (4). All patients were monitored with surface ECG; permanent telemetric endo-ECG monitoring was activated. Then, the effect of two different European telephone systems were tested: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…22 Studies of modern cellular phones and CIEDs with routine use of dedicated feedthrough filters have noted minimal or no EMI. 23, 26 In the setting of ICDs, only transient telemtery loss, 24 without clinically significant EMI has been reported. 20, 21, 25 Current recommendations indicate holding cellular phones to the ear contralateral to the CIEDs, avoiding close contact between the CIEDs and the phone, and avoiding the use of cellular phones during programming of CIEDs.…”
Section: Cellular Phonesmentioning
confidence: 99%
“…22 Studies of modern cellular phones and CIEDs with routine use of dedicated feedthrough filters have noted minimal or no EMI. 23, 26 In the setting of ICDs, only transient telemtery loss, 24 without clinically significant EMI has been reported. 20, 21, 25 Current recommendations indicate holding cellular phones to the ear contralateral to the CIEDs, avoiding close contact between the CIEDs and the phone, and avoiding the use of cellular phones during programming of CIEDs.…”
Section: Cellular Phonesmentioning
confidence: 99%
“…Barbaro et al 34 concluded that although in vitro studies under worst-case conditions demonstrate the potential of GSM cellular telephones to interfere with ICDs, generating false detection, inhibition, or reprogramming, no such serious interference was found in vivo or under realistic conditions in vitro. Occhetta et al, 35 Chiladakis et al, 36 and Tandogan et al 37 had observed no evidence of serious interferences in the functionality of the implanted defibrillator. Table 5 details other interferences in PMs and defibrillators found in papers that refer also to interferences in different medical instruments with wireless networks.…”
Section: Studies On Emimentioning
confidence: 97%
“…In 1999, two articles, Barbaro et al (1999) and Occhetta et al (1999), evaluated interferences between implantable cardioverter defibrillators (ICD) and Total Access Communication System (TACS) and GSM technologies. In Barbaro et al (1999), in vitro tests were performed with six ICDs and three phones (two GSM and one TACS) and in vivo tests with 13 patients and eight different models of ICDs with the maximum emission power at different stages of communication.…”
Section: Studies Of Electromagnetic Interference Between Implantable mentioning
confidence: 99%
“…Effects were circumscribed to the area closely surrounding the connectors. Occhetta et al (1999) performed a study on 30 patients, placing the mobile phone at different positions in several phases: call, call receiving, conversation, talking, and listening. Two different European telephone systems were tested: TACS system (Sony CM-RIII, 2 W power) and GSM system (Motorola MGI ϳ 4A11, 2 W power).…”
Section: Studies Of Electromagnetic Interference Between Implantable mentioning
confidence: 99%